MAHALLA AS AN INSTITUTE FOR INCREASING THE SPIRITUALITY OF THE YOUTH OF NEW UZBEKISTAN - Mirzokulov Izzatullo Mahkamovich (Scholar Express Journal, 2023)
Today, in order to raise the morale of young people, a more effective organization of social activities and an analysis of their activities based on new criteria are required. One of the requirements of our time was the formation of a new structure of the self-government body that meets the requirements of the time, the effective organization of its administrative system
Keywords: creativity; neighborhood; state; society